2015
DOI: 10.11113/jt.v72.3919
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Manufacturing System Computer Simulation using Taguchi Method

Abstract: In the manufacturing industry, managers and engineers are trying to sustain their competitiveness by achieving high output and productivity. There are some common problems such as waiting times, failures, reworks in production line that impose extra cost to the companies. Therefore, companies are striving to find methods in order to determine and deal with problems using different methods such as mathematical, statistical and computer simulation. The goal of this paper is to increase the total output productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
6
0
4
Order By: Relevance
“…In order to conduct the simulation experiments, model of manufacturing system was created using the Arena software. After conducting the DOE experiment the two factors which are B (Number of labor) and C (Failure time of lifter) were significant [22]. After obtaining the significant factors, the local optimum setting of the significant factors was determined using the steepest ascent method and response surface methodology approach.…”
Section: Resultsmentioning
confidence: 99%
“…In order to conduct the simulation experiments, model of manufacturing system was created using the Arena software. After conducting the DOE experiment the two factors which are B (Number of labor) and C (Failure time of lifter) were significant [22]. After obtaining the significant factors, the local optimum setting of the significant factors was determined using the steepest ascent method and response surface methodology approach.…”
Section: Resultsmentioning
confidence: 99%
“…Hatami et al [13] assessed the importance of different parameters on a production line using simulation and design of experiments (DOE) to improve productivity. In another study, the statistical Taguchi method and computer simulation were combined to investigate the impacts of main and uncontrollable parameters on the overall production output in the paint factory [14]. Dengiz et al [15] showed how the combination of regression meta-modeling techniques and simulation modeling can be applied to design and improve a real automotive manufacturing system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Taguchi method is a statistical tool, which through the process parameter levels and the experimental plan, simplifies the number of experiments and improve the method used for data analyses. It can be applied to engineering [19][20][21], manufacturing [22,23], and the supply chain [24].…”
Section: Introductionmentioning
confidence: 99%